Construction of a Family of \(C^1\) Convex Integro Cubic Splines - Tugal, Zhanlav; Renchin-Ochir, Mijiddorj (Communications in Mathematics and Applications, 2020)
We construct a family of monotone and convex \(C^1\) integro cubic splines under a strictly convex position of the dataset. Then, we find an optimal spline by considering its approximation properties. Finally, we give some examples to illustrate the convex-preserving properties of these splines.